Efektivitas Penerapan Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Numerasi Siswa - Dianra Nuroctavia Riandhany; Evan Farhan Wahyu Puadi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this study was to determine the effectiveness of the application of the Problem-Based Learning model which was characterized by differences in student’s numeracy skills in the Surface Area and Volume of Flat Sided Spaces topic at SMP Negeri 4 Kuningan between the Problem-Based Learning model and the conventional model. This research is a static group pretest-posttest design. The sample in this study was class VIII F, totaling 25 students as the experimental class, and class VIII E, totaling 32 students as the control class. Data collection techniques used are subjective tests and questionnaires. Data analysis techniques in this study were hypothesis testing and student questionnaire responses. Based on the results of statistical testing, the increase in students’ numeracy skills is in the medium category. The percentage of student’s responses to Problem-Based Learning is 51.60%. This study concludes that the numeracy skills of the students using the Problem-Based Learning model are better than the numeracy abilities of the students using conventional learning models, the improvement of student’s numeracy skills is in the medium category, and more than half of the student’s respond well to the learning model, so it can be said that Problem-Based Learning is quite effective